Taking sides Clashing views on environmental issues - Easton, Thomas A. (New York McGraw-Hill, 2011)
Environmental philisophy; Principles versus politics; Energy issues; Food and population; Toxic chemicals.
ISSN: 1091-8825
Keywords: Environmental policy; Environmental protection; Environmental ethics; Khoa học môi trường